Colour chemistry - Christie, R. M. (RSC paperbacks., 2001)
This book provides an up-to-date insight into the chemistry behind the colour of the dyes and pigments that make our world so colourful. The impressive breadth of coverage starts with a dip into the history of colour science. Colour Chemistry then goes on to look at the structure and synthesis of the various dyes and pigments, along with their applications in the traditional areas of textiles, coatings and plastics, and also the ever-expanding range of "high-tech" applications. Also discussed are some of the environmental issues associated with the manufacture and use of colour. The broad and balanced coverage presented in this book makes it ideal for students and graduates. In addition, many specialists in industry or academia will also benefit from the overview of the subject that is provided.